Expression of a second open reading frame present in the genome of tick-borne encephalitis virus strain Neudoerfl is not detectable in infected cells - Černý, Jiří; Selinger, Martin; Palus, Martin; Vavrušková, Zuzana; Tykalová, Hana; Bell-Sakyi, Lesley; Štěrba, Ján; Grubhoffer, Libor; Růžek, Daniel (Virus genes, 2016)
A short upstream open reading frame (uORF) was recently identified in the 5' untranslated region of some tick-borne encephalitis virus (TBEV) strains. However, it is not known if the peptide encoded by TBEV uORF (TuORF) is expressed in infected cells. Here we show that TuORF forms three phylogenetically separated clades which are typical of European, Siberian, and Far-Eastern TBEV subtypes. Analysis of selection pressure acting on the TuORF area showed that it is under positive selection pressure. Theoretically, TuORF may code for a short hydrophobic peptide embedded in a biological membrane. However, expression of TuORF was detectable neither by immunoblotting in tick and mammalian cell lines infected with TBEV nor by immunofluorescence in TBEV-infected mammalian cell lines. These results support the idea that TuORF is not expressed in TBEV-infected cell or expressed in undetectably low concentrations. Therefore we can assume that TuORF has either minor or no biological role in the TBEV life cycle.
Keywords: glioblastom; TuORF; Cell Line; klíště; mutace; fylogeneze; Genome, Viral; Peptide Biosynthesis; Phylogeny; Encephalitis Viruses, Tick-Borne; meduloblastom; TBEV; Neuroblastoma; Encephalitis, Tick-Borne; Immunoblotting; Animals; lidé; otevřené čtecí rámce; Humans; zvířata; klíšťová encefalitida; Ixodes; Open Reading Frames; buněčné linie; biosyntéza peptidů; genom virový; viry klíšťové encefalitidy; Mutation; uORF; Immunofluorescence; neuroblastom; Glioblastoma; Medulloblastoma